Human Development Index (HDI) in Papua Province - Nuralam, Nuralam (Journal of Social and Development Sciences, 2015)
This study aims to determine the effect of the health index, education index and the index of the economic growth of Papua Province simultaneously and partially. The analytical method used was a panel data regression analysis with Pooled Least Square method. The results showed that the index of health, education index and the index of purchasing power simultaneously and significant affect on economic growth in Papua province, while the partial test results showed that the index of education and purchasing power index affect economic growth positively and significantly, while the health index has no significant effect on the economic growth of Papua Province.